The efficiency of albendazole against gastro-intestinal nematodes, dictyocaulus filaria and moniezia spp. in sheep - Bilâl Dik; Suphi Gülbahçe (Eurasian Journal of Veterinary Sciences)
Activity of albendazole was determined against gastrointestinal nematodes, D. filaria and Moniezia spp, in naturally infected twenty one sheep. They were divided into four groups. Albendazole was administered to the first, second and. third groups at the rates of 3.8 mg, 7.5 mg and 10 mg/kg respectively. Fourth group was kept as a control. It was showed that albendazole was 100 % effective on the gastrointestinal nematodes and Moniezia spp. at all doses in faecal examinations made at the 4 th and 11 th days. Efficacy of albendazole 3.8 mg, 7.5 mg and 10 mg/kg doses against D. filaria was 99 %, 100 % and 98 % respectively at the 4 th day after treatment. D. filaria larvae were not found in the faeces of all terated sheep at the 11 th day.